Challenges of translation process research at the workplace - Ehrensberger-Dow, Maureen (MonTi Monografías de Traducción e Interpretación, 2015)
Translation usually takes place at translators’ workplaces, yet much translation process research refers to data collected under controlled conditions such as the classroom or the lab. Pursuant with recent descriptions of translation as a situated activity comes the necessity of investigating that activity where and when it occurs. Many of the methods that have proved useful in the lab have also been applied in the field, and some of the challenges associated with investigating translation at the workplace are common to any kind of empirical translation research. However, certain workplace constraints present special challenges to everyone involved. Some solutions that were developed for a workplace study in Switzerland may prove useful in other investigations and might allow new questions to emerge in this developing field.